Consumer perception of chicken meat from broilers fed natural pigment sources (2018)
Consumer perception of chicken meat obtained from broiler chickens fed diets containing natural pigment sources was investigated. One hundred and sixty one-day-old Arbor acre broiler chicks were randomly allotted to 5 dietary treatments with 4 replicates and 8 birds per replicate in a completely randomised design. Test ingredients were introduced at day 21(the finisher stage). TA- Control, TB- Roselle calyx, TC- Orange peels, TD- Baobab leaves, TE- Moringa leaves (each at 4% inclusion rates). Two birds per replicate were slaughtered at 8 weeks and physico-chemical and carcass visual and textural attributes were assessed. Results revealed that pH values (p<0.05) ranged from 6.49 (Treatments A and E) to 6.25 (Treatment B) while shear force ranged (p<0.05) from 1.25 (Treatment B) to 0.53 (Treatment C). No (p>0.05) variation was observed on cooking yield and loss in all treatments. Significant differences were observed in carcass assessment scores for all treatments. Treatment E (Moringa) had highest value (6.95) for skin colour which showed a high degree of yellowness while treatment C (Orange peel) had highest score (5.48) for muscle colour (highly pinkish). Treatment B (Roselle calyx) had lowest values for skin (3.13-whitish) and muscle (3.50-whitish) colours. High overall acceptability score was however recorded in orange peel supplemented diet (Treatment C). The study concludes that, orange peels can be incorporated at 4% inclusion level in broiler chicken diet to increase carcass attractiveness and aid increased consumer acceptance.